2000
DOI: 10.1046/j.1365-2842.2000.00582.x
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical calculation of human TM joint loading with jaw opening

Abstract: A three-dimensional, static mathematical calculation of the stomatognathic system was done to predict total temporomandibular joint (TMJ) loading at different levels of jaw opening. The model assumed that muscle forces acting on the mandible could be simulated by a combination of contractile components (CCs) and elastic components (ECs) and that static equilibrium existed within the body of the mandible. The model also imposed the constraint that any generated joint reaction force would act on the centre of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Functional appliance therapy is believed to place the mandible in a protrusive position, causing the condyle to be unseated caudally and ventrally from the articular fossa, while forced mouth opening is believed to cause a compressive force between the articular eminence and the mandibular condyle (Fujisawa et al ., 2003). A possible explanation for both functional appliance therapy and forced mouth opening causing similar effects in the mandibular condylar cartilage is that the mandibular condylar cartilage responds similarly to different types of loading compression for forced mouth opening (Kuboki et al ., 2000) and tension for functional appliance therapy (Gupta et al ., 2009; Panigrahi and Vineeth, 2009). Another possible explanation is that forced mouth opening and functional appliance therapy influence the masticatory muscles in such a way that the actual deformational strains within the mandibular condylar cartilage are similar for both.…”
Section: Discussionmentioning
confidence: 99%
“…Functional appliance therapy is believed to place the mandible in a protrusive position, causing the condyle to be unseated caudally and ventrally from the articular fossa, while forced mouth opening is believed to cause a compressive force between the articular eminence and the mandibular condyle (Fujisawa et al ., 2003). A possible explanation for both functional appliance therapy and forced mouth opening causing similar effects in the mandibular condylar cartilage is that the mandibular condylar cartilage responds similarly to different types of loading compression for forced mouth opening (Kuboki et al ., 2000) and tension for functional appliance therapy (Gupta et al ., 2009; Panigrahi and Vineeth, 2009). Another possible explanation is that forced mouth opening and functional appliance therapy influence the masticatory muscles in such a way that the actual deformational strains within the mandibular condylar cartilage are similar for both.…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria were: (a) history of speech or swallowing deficit, (b) TMJ dysfunction, (c) taking medications that could affect swallowing or neurological functions, and (d) engaged in any type of swallowing-related strength training program for at least 1 year prior to this study. TMJ dysfunctions were included among exclusion criteria because resistive JOE, which requires resistive jaw opening, could lead to worsening of the symptoms [10]. Participants were examined by an occupational therapist with a major in dysphagia therapy.…”
Section: Methodsmentioning
confidence: 99%
“…They chose resistance-free JOE to avoid excessive stress on the temporomandibular joint (TMJ). Kuboki et al [10] reported that the more one opens her or his mouth, the greater the strength of the compression force between the TMJ condyle and the articular eminence. In the state where resistance is applied when the mouth is opened, the compressive force would dramatically increase; however, to maximize the improved strength due to exercise over time, the absolute value of the load placed on the muscle must be progressively increased according to the incremental strength of the participant [11].…”
Section: Introductionmentioning
confidence: 99%
“…Since we have established a 3-D mathematical model of the human stomatognathic system with the mouth opened, and recognize that there is a compressive force between the articular eminence and the mandibular condyle during jaw opening (Kuboki et al, 2000), we thought that modification of the forced-jaw-opening protocol would enable us to produce OA-like lesions in the TMJ. We then selected a repetitive, steady mouthopening protocol to produce continuous compression onto the articular cartilage, since we know that continuous compression does induce higher cartilage deformation than intermittent compression in an in vitro experimental indentation model of the pig TMJ articular cartilage (Kuboki et al, 1997) and an in vivo radiographic joint space measurement (Takenami et al, 1999).…”
Section: Introductionmentioning
confidence: 99%